Two-color infrared predissociation spectroscopy of C₆H₆²⁺ isomers using helium tagging - Jašík, Juraj; Gerlich, Dieter; Roithová, Jana (The journal of physical chemistry. A, 2015)
Two-color IR-IR isomer selective predissociation spectra of helium-tagged C6H6(2+) are presented. The dications are generated via electron bombardment of either benzene or 1,3-cyclohexadiene. After mass selection they are injected into a 2.6 K cold ion trap where the presence of a dense He buffer gas not only cools them but also leads to He attachment. The ion ensemble is exposed to one or two intense IR pulses from optical parametric oscillators (OPOs) (1200-3100 cm(-1)) before it is extracted, mass analyzed, and detected. On the basis of a comparison with theoretical predictions, the resulting spectral features allow us to separate and assign different isomers of C6H6(2+) dications. Compression of the ion cloud very close to the axis of the linear quadrupole trap and coaxial superposition of well-collimated laser beams results in the fragmentation of almost all helium complexes at specific wavelengths. This unique feature enables us to record fluence-dependent attenuation curves for individual absorption bands and thus determine not only absorption cross sections but also the composition of the ion mixture.